Preparation method of Co / Cu nano-alloy catalyst for reducing ammonia through electro-catalysis of nitrate

By preparing Co/Cu nanoalloy catalysts, the problem of Faraday efficiency and low yield in nitrate reducing ammonia reaction is solved, and efficient ammonia production is achieved, which is suitable for industrial applications.

CN119553302APending Publication Date: 2025-03-04HEILONGJIANG UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411776968.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, the Faraday efficiency and yield of nitrate reducing ammonia are low, and the activity and selectivity of the electrocatalyst are poor, resulting in a greater impact on the hydrogen evolution reaction of the competitive reaction.

Method used

Using the preparation method of Co/Cu nanoalloy catalyst, the Co/Cu nanoalloy catalyst was prepared by immersing foamed copper in a solution containing ammonium persulfate and sodium hydroxide oxidizing to obtain Cu(OH)2, and then adding Co elements during the electrochemical deposition process, and finally undergoing high-temperature heat treatment in a hydrogen/argon atmosphere to prepare a Co/Cu nanoalloy catalyst with nanoneedle structure.

Benefits of technology

The prepared Co/Cu nano alloy catalyst showed excellent Faraday efficiency and yield in nitrate reducing ammonia reaction, with ammonia yield as high as 16762.68ug h-1cm-2, and the Faraday efficiency remained above 90%, and was well stable under alkaline conditions, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553302A_ABST
    Figure CN119553302A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Co / Cu nano-alloy catalyst for reducing ammonia through electro-catalysis of nitrate, and belongs to the technical field of electro-catalysts and preparation thereof. The invention solves the problems of low Faraday efficiency and low yield in the process of converting nitrate into ammonia through electro-catalysis in the prior art. According to the invention, Cu and Co are compounded to prepare the catalyst of nitrate reduced ammonia with a nanoneedle structure, and the catalyst shows excellent Faraday efficiency and yield in nitrate reduced ammonia. A test result shows that the ammonia yield of the prepared Co / Cu nano-alloy catalyst reaches up to 16762.68 ugh <-1 > cm <-2 > and the Faraday efficiency is kept above 90% when the Co / Cu nano-alloy catalyst is in a mixed solution of 0.1 mol / L KNO3 and 1 mol / L KOH and the RHE is-0.5 Vvs.RHE. In addition, when the catalyst is at-0.4 V vs.RHE, the ammonia yield and the Faraday efficiency are kept stable during 10 cycles of the reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a Co / Cu nano alloy catalyst for electrocatalytically reducing ammonia with nitrate, and belongs to the technical field of electrocatalysts and preparation thereof. Background Art

[0002] Ammonia is an indispensable value-added raw material and fertilizer for the agricultural and industrial sectors. Ammonia has the potential to be a carbon-free energy carrier due to its high energy density (4.3kWh kg -1 ) and hydrogen storage capacity (17.6%). Conventional industrial ammonia production relies heavily on the energy-intensive Haber-Bosch process, which requires harsh reaction conditions (temperature 400-600°C, pressure 10-30MPa) and high energy consumption (~2% of annual energy supply), and leads to large amounts of carbon dioxide emissions (~400 metric tons per year).

[0003] Electrochemical ammonia reduction from nitrates has become an attractive approach because it can be operated in aqueous solutions containing nitrates, even at very low concentrations and at room temperature. In addition, nitrates are a major environmental pollutant often found in agricultural runoff and industrial wastewater, posing a serious threat to human health. Therefore, in order to achieve a green ammonia era, it is crucial to develop a greener reaction to replace the Haber-Bosch process.

[0004] However, the conversion of nitrate to ammonia is a multi-step reaction involving the transfer of 8 electrons and 9 protons to synthesize an ammonia molecule. So far, the ambiguous reaction mechanism of nitrate reduction to ammonia has led to poor activity and selectivity for ammonia. In addition, the main competing reaction for the electrocatalytic nitrate reduction to ammonia is the hydrogen evolution reaction (HER) at the cathode, which greatly affects the Faradaic efficiency and yield of the catalyst for the reduction of ammonia. Therefore, efficient electrocatalysts suitable for industrial nitrate reduction to ammonia need to be improved and developed. Summary of the invention

[0005] Aiming at the problems of low Faraday efficiency and low yield in the existing conversion of nitrate into ammonia, the present invention provides a method for preparing a Co / Cu nano alloy catalyst for electrocatalytic nitrate reduction of ammonia.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a method for preparing a Co / Cu nano alloy catalyst, which comprises the following steps:

[0008] (1) immersing the foamed copper in an immersion solution containing ammonium persulfate and sodium hydroxide, allowing it to stand for oxidation, and drying it to obtain Cu(OH)2;

[0009] (2) using the Cu(OH)2 obtained in (1) as a cathode and an aqueous solution containing a Co element as an electrolyte solution, and performing electrochemical deposition treatment to obtain a Cu(OH)2-Co precursor;

[0010] (3) After the Cu(OH)2-Co precursor is dried, it is subjected to high-temperature heat treatment in a hydrogen / argon atmosphere to obtain a Co / Cu nanoalloy catalyst.

[0011] It is further defined that the concentration of ammonium persulfate in the impregnation solution of (1) is 1 to 5 mmol / L.

[0012] It is further defined that the concentration of sodium hydroxide in the impregnation solution of (1) is in the range of 1 to 5 mmol / L.

[0013] It is further defined that the static oxidation time in (1) is 10 to 30 minutes.

[0014] It is further defined that the concentration of the Co element in the electrolyte solution of (2) is 10 to 100 mmol / L, and the Co element comes from cobalt sulfate, cobalt nitrate, cobalt phosphate or cobalt acetate.

[0015] It is further defined that the concentration of the Co element is 15 to 30 mmol / L.

[0016] Furthermore, the concentration of the Co element is 20 mmol / L or 25 mmol / L.

[0017] It is further defined that the electrolyte solution of (2) contains an auxiliary electrolyte at a concentration of 10 to 30 mmol / L, and the auxiliary electrolyte is sulfuric acid, nitric acid, sodium sulfate, sodium chloride or potassium chloride.

[0018] It is further defined that the concentration of the auxiliary electrolyte is 20 mmol / L.

[0019] It is further defined that in the electrochemical deposition process of (2), the anode is a carbon rod, the reference electrode is Ag / AgCl, the applied voltage is -0.1 to -2 V, the scan rate is 5 to 100 mV, and the number of deposition cycles is 1 to 10 cycles.

[0020] Furthermore, the applied voltage is limited to -0.1 to -0.4V.

[0021] Furthermore, the applied voltage is limited to -0.8 to -1.2V.

[0022] Furthermore, the applied voltage is limited to -1.2 to -1.6V.

[0023] Furthermore, the applied voltage is limited to -1.6 to -2V.

[0024] Further limiting, the sweep rate is 10 mV, 20 mV, 40 mV, 60 mV or 80 mV.

[0025] Further limited, the number of deposition turns is 2 turns, 3 turns, 4 turns, 5 turns, 6 turns, 7 turns, 8 turns or 9 turns.

[0026] It is further defined that the high temperature heat treatment process of (3) is: heating to 150-650°C at a heating rate of 1-7°C / min and keeping the temperature for 100-500min.

[0027] It is further defined that the high temperature heat treatment temperature is 250°C, 350°C, 450°C or 550°C.

[0028] It is further defined that the high temperature heat treatment time is 200 min, 300 min or 400 min.

[0029] Further defined, the heating rate is 2°C / min, 3°C / min, 4°C / min, 5°C / min or 6°C / min.

[0030] The second object of the present invention is to provide a Co / Cu nano alloy catalyst prepared by the above method.

[0031] The third object of the present invention is to provide an application of the above-mentioned Co / Cu nano alloy catalyst, specifically for electrocatalytic nitrate reduction to produce ammonia.

[0032] Beneficial effects:

[0033] 1. The present invention prepares a catalyst for nitrate reduction of ammonia by composite Cu and Co with a nanoneedle structure, which has uniform element distribution, good stability, excellent charge transfer ability, and excellent Faradaic efficiency and yield in nitrate reduction of ammonia. Test results show that the prepared Co / Cu nano alloy catalyst has an ammonia yield of up to 16762.68ug h in a mixed solution of 0.1mol / LKNO3 and 1mol / LKOH at -0.5V vs.RHE. -1 cm -2 , and the Faradaic efficiency remained above 90% at all test voltages. In addition, the ammonia yield and Faradaic efficiency of the catalyst remained stable during 10 cycles of reaction at -0.4 V vs. RHE.

[0034] 2. The Co / Cu nano alloy catalyst prepared by the present invention is suitable for alkaline conditions, and the preparation method is simple, suitable for large-scale production, and has good industrial applicability. And a highly active catalyst can be obtained by adjusting the composition and concentration of the electrodeposition precursor solution, the deposition voltage range, the number of deposition cycles, the heat treatment temperature, the heat treatment holding time, the heat treatment heating rate, etc., so as to meet the different requirements of the reaction for catalytic performance in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM photo of the Cu catalyst prepared in Comparative Example 1;

[0036] Figure 2 This is a SEM photo of the Co / Cu catalyst prepared in Example 1;

[0037] Figure 3 The current density versus voltage curve comparison diagram of the catalysts prepared in Example 1 and Comparative Examples 1-2;

[0038] Figure 4 This is a comparison chart of the Faraday efficiencies of the catalysts prepared in Example 1 and Comparative Examples 1-2;

[0039] Figure 5 This is a comparison chart of the yield of ammonia prepared using the catalysts prepared in Example 1 and Comparative Examples 1-2;

[0040] Figure 6 This is a performance comparison chart of the catalysts prepared in Example 1 and Comparative Examples 1-2 after 10 cycles of testing at a voltage of -0.4 V vs. RHE. DETAILED DESCRIPTION

[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0044] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0045] Example 1

[0046] (1) The hole diameter is 0.1 mm, the thickness is 0.5 mm, and the area is 1 cm -2 The commercial copper foam was ultrasonically cleaned in anhydrous ethanol, dilute hydrochloric acid, and deionized water solution for 15 min.

[0047] (2) The copper foam treated by (1) was immersed in an impregnation solution containing ammonium persulfate and sodium hydroxide (the concentrations of ammonium persulfate and sodium hydroxide solutions were 1.5 mmol / L and 5 mmol / L, respectively), and allowed to stand for oxidation treatment for 30 minutes to obtain Cu(OH)2.

[0048] (3) Using the Cu(OH)2 obtained in step (2) as the cathode, the carbon rod as the anode, and Ag / AgCl as the reference electrode, cyclic voltammetric electrodeposition was performed in a newly prepared mixed solution of CoCl·6H2O (30mmol / L) and Na2SO4 (50mmol / L) at -0.8 to -1.2V vs.Ag / AgCl, a scan rate of 80mV, and a deposition cycle rate of 10C to obtain a Cu(OH)2-Co precursor.

[0049] (4) The Cu(OH)2-Co precursor obtained in step (3) is subjected to high-temperature heat treatment in a hydrogen / argon atmosphere, specifically, the temperature is increased to 350°C at a heating rate of 5°C / min, kept at that temperature for 400 min, and naturally cooled to room temperature to obtain a Co / Cu catalyst.

[0050] Comparative Example 1

[0051] The difference between this comparative example and Example 1 is that step (3) is not performed, and the Cu(OH)2 obtained in step (2) replaces the Cu(OH)2-Co precursor in step (4) for high-temperature heat treatment. The remaining process steps and parameter settings are the same as those in Example 1 to obtain a Cu catalyst.

[0052] Comparative Example 2

[0053] The difference between this comparative example and Example 1 is that steps (1) and (2) are not performed, carbon cloth is used to replace Cu(OH)2 in step (3) as the cathode, and the remaining process steps and parameter settings are the same as those in Example 1 to obtain a Co / CC catalyst.

[0054] Effect example

[0055] (1) The microstructures of the Co / Cu catalyst and the Cu catalyst prepared in Example 1 and Comparative Example 1 were characterized. Figure 1 and Figure 2 As shown in the figure, it can be seen that the structure of the Cu catalyst is Cu nanoneedles, while the Co / Cu catalyst is a Cu nanoneedle structure with Co loaded on the surface.

[0056] (2) The current density of the catalysts prepared in Example 1 and Comparative Examples 1-2 was tested. The results are as follows: Figure 3 As shown by Figure 3 It can be seen that the current density of the Co / Cu catalyst prepared in Example 1 greatly exceeds that of the Cu catalyst and Co / CC catalyst prepared in Comparative Examples 1-2. This is because the Co loaded on the Cu nanoneedles improves the ability of H2O to decompose H protons and accelerates the subsequent hydrogenation reaction of nitrate reduction.

[0057] (3) The Faraday efficiency of the catalysts prepared in Example 1 and Comparative Examples 1-2 was measured at different voltages in a mixed solution of 1 mol / L KOH and 0.1 mol / L KNO3. The results are as follows: Figure 4 As shown by Figure 4 It can be seen that the Faradaic efficiency of the Co / Cu catalyst is maintained above 90%.

[0058] (4) The catalysts prepared in Example 1 and Comparative Examples 1-2 were placed in a mixed solution of 1 mol / L KOH and 0.1 mol / L KNO3, and the ammonia yield was measured at different voltages. The results are as follows: Figure 5 As shown by Figure 5 It can be seen that the ammonia yield of the Co / Cu catalyst prepared in Example 1 is much greater than that of the Cu catalyst and Co / CC catalyst prepared in Comparative Examples 1-2. This is because the loading of Co accelerates the reduction of nitrates. In addition, as the voltage shifts negatively, the ammonia yield of the Co / Cu catalyst increases continuously, and at -0.5 V vs. RHE, the yield reaches 16762.68 ug h -1 cm -2 .

[0059] (5) Figure 6 This is a performance diagram of the Co / Cu catalyst prepared in Example 1 after 10 cycles of testing at -0.4 V vs. RHE. It can be seen from the figure that the Faraday efficiency and ammonia yield of the catalyst remained stable during the 10 cycles of testing, indicating that the Co / Cu catalyst has good stability.

[0060] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a Co / Cu nano alloy catalyst, characterized in that: include: (1) immersing the foamed copper in an immersion solution containing ammonium persulfate and sodium hydroxide, allowing it to stand for oxidation, and drying it to obtain Cu(OH)2; (2) using the Cu(OH)2 obtained in (1) as a cathode and an aqueous solution containing a Co element as an electrolyte solution, and performing electrochemical deposition treatment to obtain a Cu(OH)2-Co precursor; (3) After the Cu(OH)2-Co precursor is dried, it is subjected to high-temperature heat treatment in a hydrogen / argon atmosphere to obtain a Co / Cu nanoalloy catalyst.

2. The preparation method according to claim 1, characterized in that: The concentration of ammonium persulfate in the impregnation solution of (1) is 1 to 5 mmol / L.

3. The preparation method according to claim 1, characterized in that: The concentration of sodium hydroxide in the impregnation solution of (1) is in the range of 1 to 5 mmol / L.

4. The preparation method according to claim 1, characterized in that: (1) The static oxidation time is 10 to 30 minutes.

5. The preparation method according to claim 1, characterized in that: The concentration of the Co element in the electrolyte solution of (2) is 10 to 100 mmol / L, and the Co element comes from cobalt sulfate, cobalt nitrate, cobalt phosphate, cobalt acetate or cobalt chlorate.

6. The preparation method according to claim 1, characterized in that: The electrolyte solution of (2) contains an auxiliary electrolyte with a concentration of 10 to 30 mmol / L, and the auxiliary electrolyte is sulfuric acid, nitric acid, sodium sulfate, sodium chloride or potassium chloride.

7. The preparation method according to claim 1, characterized in that: In the electrochemical deposition process of (2), the anode is a carbon rod, the reference electrode is Ag / AgCl, the applied voltage is -0.1 to -2 V, the scan rate is 5 to 100 mV, and the number of deposition cycles is 1 to 10 cycles.

8. The preparation method according to claim 1, characterized in that: The high temperature heat treatment process of (3) is as follows: heating to 150-650°C at a heating rate of 1-7°C / min and keeping the temperature for 100-500min.

9. A Co / Cu nano alloy catalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the Co / Cu nano alloy catalyst according to claim 9, characterized in that: Used for electrocatalytic nitrate reduction to produce ammonia.

Citation Information

Cited By

  • Preparation method and application of CuFe Prussian blue analogue cubic array electrocatalyst

    CN119824458A

  • Preparation method and application of copper-based electrode material

    CN120556069A

  • Preparation method and application of a copper-based electrode material

    CN120556069B